2009
DOI: 10.1039/b911265k
|View full text |Cite
|
Sign up to set email alerts
|

A catenated imidazole-based coordination polymer exhibiting significant CO2 sorption at low pressure

Abstract: A robust, porous, catenated coordination polymer based on a neutral, flexible imidazole-derived tripodal ligand (a 'tripodal imidazole framework', TIF) reversibly absorbs vapours and gases, particularly CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Hupp and co-workers 306 reported an unusual MOF structure, 538, which was composed of metal imidazolates rather than imidazolium salts. 307 As shown in Scheme 104, the preparation of 538 was accomplished by the reaction of the tripodal imidazole compound 537 (1 equiv) and CoCl 2 •6H 2 O (1 equiv) in a solvent mixture of DMF, ethylene glycol, and pyridine at 140 °C for 72 h. The crystal structure of 538 revealed that each imidazole coordinated to one cobalt atom creating two interweaving two-dimensional sheets, which formed one-dimensional channels perpendicular to the plane with a diameter of 8.5 Å.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Hupp and co-workers 306 reported an unusual MOF structure, 538, which was composed of metal imidazolates rather than imidazolium salts. 307 As shown in Scheme 104, the preparation of 538 was accomplished by the reaction of the tripodal imidazole compound 537 (1 equiv) and CoCl 2 •6H 2 O (1 equiv) in a solvent mixture of DMF, ethylene glycol, and pyridine at 140 °C for 72 h. The crystal structure of 538 revealed that each imidazole coordinated to one cobalt atom creating two interweaving two-dimensional sheets, which formed one-dimensional channels perpendicular to the plane with a diameter of 8.5 Å.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…[102][103][104][105][106][107][108] Interestingly, when the robust solvent-free framework I was immersed into a solution of iodine in cyclohexane, its hexagonally-arranged channels allowed iodine to form very intriguing polyiodine chains. The iodine-captured framework of I, I_I 2 , was structurally characterized by X-ray crystallography ( Table 1).…”
Section: Characterization Of Current-voltage (I-v)mentioning
confidence: 99%
“…19 There are several members of this class of MOFs, and many of them have been reported for potential roles in interesting applications such as large, selective uptake of carbon dioxide. [20][21][22] One particularly interesting member of the ZIF family and the one investigated here is ZIF-8 (2-methylimidazole zinc salt). ZIF-8 has been demonstrated in many applications including the kinetic separation of propane/propylene, 23 the separation of hydrogen, 24 and the oxidation of CO in a ZIF-8 impregnated with gold.…”
Section: Introductionmentioning
confidence: 99%
“…ZIFs are formed by the crystallization of a transition metal species bound to the nitrogens of an imidazole compound and are so named because of their structural similarities to many zeolites (including characteristic angles of 145°, the preferred Si−O−Si angle seen in many zeolites) . There are several members of this class of MOFs, and many of them have been reported for potential roles in interesting applications such as large, selective uptake of carbon dioxide. …”
Section: Introductionmentioning
confidence: 99%